One-step synthesis of CoO/g-C3N4 composites by thermal decomposition for overall water splitting without sacrificial reagents. Issue 10 (5th September 2017) - Han, Mumei; Wang, Huibo; Zhao, Siqi; Hu, Lulu; Huang, Hui; Liu, Yang
Abstract : 10%CoO/g-C3 N4 exhibits good photocatalytic performance under visible light irradiation without any sacrificial reagents. Abstract : Using photocatalysts to split water into hydrogen and oxygen is a promising way to produce renewable energy. Efficient and stable photocatalysts are desired for overall water splitting under visible light. We demonstrate that the cobalt(ii ) oxide (CoO)/graphitic carbon nitride (CoO/g-C3 N4 ) composites synthesized by a one-step thermal decomposition method exhibit enhanced photocatalytic efficiency for overall water splitting without sacrificial reagents. 10%CoO/g-C3 N4 exhibits optimal photocatalytic performance, where H2 and O2 evolution rates are, respectively, 0.46 μmol h −1 and 0.21 μmol h −1 under visible light irradiation without any sacrificial reagents. It is worth mentioning that the H2 and O2 production almost approaches the stoichiometric ratio 2 : 1. The enhanced photocatalytic activity of CoO/g-C3 N4 may be ascribed to the efficient charge separation and fast decomposition of H2 O2 by CoO.